Meningkatkan Kepatuhan Syariah dalam Perbankan Syariah di Indonesia: Penyimpangan, Tantangan, dan Upaya Perbaikan - Nurul Monika Larasati; Rayyan Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Islamic banking in Indonesia has experienced significant growth alongside increasing public interest in financial products that comply with Islamic principles. However, in practice, there are still challenges that prevent Islamic banking products and services from fully meeting Sharia standards. Some of the issues include the use of wadiah contracts in current accounts, which deviate from their original concept of safekeeping; the application of murabahah contracts for financing consumptive goods, which contradicts their intended purpose; the frequent misuse of ijarah muntahia bit tamlik (IMBT) contracts for speculative purposes; and mudharabah contracts with unfair profit-sharing ratios. Additionally, factors such as a lack of understanding of Islamic finance, competitive pressure from conventional banks, inadequate supervision, and differing interpretations of Sharia law further hinder the implementation of fully Sharia-compliant products and services. To resolve these challenges, various efforts are needed, including enhancing the quality of human resources through education and training, implementing stricter supervision by relevant authorities, developing clearer and more comprehensive operational standards, and fostering closer collaboration with Islamic scholars for accurate legal guidance. These steps are expected to help Islamic banking fully adhere to Sharia principles, increase public trust, and support the growth of the Islamic finance industry.